DOES COVID-19 REALLY IMPACT ON EXPORT FISHERIES BUSINESS? (Case Study: Kolaka Regency, Southeast Sulawesi, Indonesia) - Campina Illa Prihantini; Muhtar Amin; Nurfadila Nurfadila; Nursalam Nursalam; Yuli Purbaningsih; Ramlah Saleh (Jurnal Sosial Ekonomi Kelautan dan Perikanan, 2022)
This study aims to analyze the impact of the COVID-19 pandemic on fisheries sector, including the export fishery business. Tanggetada Subdistrict, located in Kolaka Regency, Southeast Sulawesi Province, is one of the suppliers of export fishery commodities through Makassar City in South Sulawesi Province. The analytical method used is a different test of costs, revenues, and income in the export fishery business before and during the COVID-19 pandemic. The selected sample is four export fishery business actors using purposive sampling. The data used are primary data in the form of export fishery business data from each respondent gathered from interviews through questionnaires. While secondary data is supporting data from the Central Statistics Agency, the Ministry of Marine Affairs and Fisheries as well as several research results on the topic of scientific journals. The data then were analyzed using income analysis, which was carried out with a different test using the SPSS application. The results of the analysis of the different tests (paired sample t-test) show that there are significant differences in the income level of the export fishery of the four entrepreneurs before and during the Covid-19 pandemic.